Fluorination as an effective tool to increase the open-circuit voltage and charge carrier mobility of organic solar cells based on poly(cyclopenta[2, 1-b:3, 4-b′]dithiophene-alt-quinoxaline) copolymers. Issue 6 (23rd December 2014) - Verstappen, Pieter; Kesters, Jurgen; Vanormelingen, Wouter; Heintges, Gaël H. L.; Drijkoningen, Jeroen; Vangerven, Tim; Marin, Lidia; Koudjina, Simplice; Champagne, Benoît; Manca, Jean; Lutsen, Laurence; Vanderzande, Dirk; et al.
Abstract : Quinoxaline fluorination leads to enhanced properties and efficiencies in PCPDTQx-based polymer solar cells. Abstract : The effect of fluorination on the optoelectronic properties and the polymer : fullerene solar cell characteristics of PCPDTQx-type (poly4-(2′-ethylhexyl)-4-octyl-4 H -cyclopenta[2, 1- b :3, 4- b ′]dithiophene- alt -2, 3-bis[5′-(2′′-ethylhexyl)thiophen-2′-yl]quinoxaline) low bandgap copolymers is reported. The introduction of fluorine atoms on the quinoxaline constituents is an effective way to lower the HOMO and LUMO energy levels of the alternating copolymers, resulting in an enhanced open-circuit voltage for the devices based on the fluorinated polymers (∼0.1 V per F added). Furthermore, fluorination also improves the charge carrier mobility in the bulk heterojunction blends. Despite the formation of unfavorable photoactive layer morphologies, the best solar cell performance is obtained for the copolymer prepared from the difluorinated quinoxaline monomer, affording a power conversion efficiency of 5.26% under AM 1.5G irradiation, with an open-circuit voltage of 0.83 V, a short-circuit current density of 11.58 mA cm −2 and a fill factor of 55%.